Small Molecule “Silmitasertib” Repurposed as Inhibitor of Transforming Growth Factor Beta 1 for the Development of Therapeutics for Oral Submucous Fibrosis - Boreak, Nezar (Biomed Res Int, 2021)
Oral submucous fibrosis (OSMF) is considered a premalignant condition characterized by aggressive fibrosis of the submucosal tissues of the oral cavity reflecting its malignant transformation potential. Activation of transforming growth factor beta (TGF-β) signaling has been reported to lead increased collagen production and fibrosis. Recently, significant upregulation of TGF-β1 has been reported in OSMF as compared to normal tissues. Therefore, inhibition of the TGF-β1 may pave for the development of therapeutics of OSMF. Based on the structure-assisted drug designing, we found “silmitasertib” as potent inhibitor of TGF-β1. We suggest that this molecule can be validated and implemented for the treatment of OSMF.